دراســة الخصائـص الميكانيكيـة والفيزيائيـة لخرسانـة رمـل المحاجـر المعـززة بالأليـاف المعدنيـة - عبــد الرحمــان, درقيــش; فتحــي, بــن ناصــر (université d'eloued, 2020)
Abstract The main objective of this study is to try to exploit quarry sand, which is abundant and problematic in storage and environmental impact, this is not to be used in a large amount, which makes us think about how to value it by exploiting it in various construction fields, as an alternative to valleys sand or non-renewable sea sand that constitutes their use is environmental problems, on the other hand, concrete in general suffers from a noticeable weakness of resistance in hot and dry climates in anticipation of cracking and shrinkage problems, for this reason, we considered strengthening them with mineral fibers in order to avoid weakness to obtain acceptable physical and mechanical properties where we exploited sand quarries are not an octagon for the area of BouSaada, the state of M'sila and its reinforcement with refractory mineral fibers and interest in identifying the properties of the materials that make up the concrete mixture through a series of standardized experiments, and studying how to obtain the optimum composition in terms of operation on one hand, and in terms of mechanical properties, on the other. Taking into account most of the factors that can affect these properties, such as: fiber ratio. ملخص الهدف الأساسي من هذه الدراسة هو محاولة استغلال رمل المحاجر، المتواجد بكثرة والمسبب لإشكالية في التخزين و التأثير البيئي ،وهذا لعدم استغلاله بكمية كبيرة مما يجعلنا نفكر في كيفية تثمينه باستغلاله في المجالات الإنشائية المختلفة ، وذلك كبديل لرمل الوديان أو رمل البحار غير المتجددة و التي يشكل استعمالها مشاكل بيئية ، ومن جهة أخرى فان الخرسانة بصفة عامة تعاني من الضعف الملحوظ للمقاومة في الأجواء الحارة و الجافة تحسبا لظهور مشاكل التشقق و الانكماش ، ولهذا فكرنا في تعزيزها بالألياف المعدنية بغية تفادي هذا الضعف و الحصول على خصائص فيزيائية و ميكانيكية مقبولة حيث قمنا باستغلال رمل المحاجر غير مثمن لمنطقة بوسعادة ولاية مسيلة وتعزيزه بالألياف المعدنية المعكوفة والاهتمام بالتعرف على خصائص المواد المكونة للخليط الخرسانة من خلال سلسلة من التجارب المعيارية ،ودراسة كيفية الحصول على التركيبة الأمثل من حيث التشغيل من جهة ومن حيث الخصائص الميكانيكية من جهة أخرى. آخذين بعين الاعتبار معظم العوامل التي يمكن أن تؤثر على هذه الخصائص مثل: نسبة الألياف.
مواد في الهندسة المدنية
Keywords: sand quarries ,fiber ,concrete , pressure resistance, tensile strength, shrinkage , elasticity; رمل المحاجر ، الألياف ،الخرسانة، الضغط ،الشد ،الانكماش ، معامل المرونة